Indonesian Lecturers' Perceptions of ChatGPT as an Automated Essay Scorer (AES) - Sanjaya, Kharisma Adhi; Abung, Ivanna Najwa; Oktarian, Rizky Ramadhan Tri; Addiena, Maisarah; Husna, Nida (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores the perceptions of English lecturers toward GPT-5 as an Automated Essay Scoring (AES) tool, specifically focusing on its accuracy in content-related evaluation within Indonesian higher education. A qualitative approach was employed, using convenience sampling to select three lecturers at State Islamic University Syarif Hidayatullah Jakarta for semi-structured interviews. Data were analyzed using thematic analysis. Findings indicate that ChatGPT effectively recognizes linguistic features and content coherence, making it a capable co-rater when prompts and rubrics are clearly defined. However, lecturers expressed